Photoionization and Photodissociation Rates across a Solar Cycle - Luke Moore; Russell Mapaye (The Planetary Science Journal)
Unattenuated photoionization and photodissociation rate coefficients are calculated using solar spectral irradiance measurements across a continuous solar cycle spanning 2004–2014. These rates are organized by corresponding daily F _10.7 P indices, where F _10.7 P $=\,\frac{1}{2}(F_{10.7}+F_{10.7}A)$ , F _10.7 is a common historical proxy for solar ultraviolet and soft X-ray activity, and F _10.7 A is its 81 day running average. Power-law relationships are established between F _10.7 P and photo rate coefficients for 48 reactions across 12 of the most common species in solar system upper atmospheres and cometary comae: H, H _2 , OH, H _2 O, O, O _2 , C, CO, CO _2 , N _2 , N, and CH _4 . The resulting coefficients are broadly consistent with previous estimates and provide a practical, efficient means of estimating photoionization and photodissociation rates for a range of planetary and cometary applications.